Kepemilikan Institusional, Kinerja Perusahaan, dan Efek Moderasi dari Kepemilikan Institusional Aktif - Rahmat Setiawan; Moh Maulidi Syarif (Jurnal Bisnis dan Keuangan, 2019)
This research investigate impact of institutional ownership on firm performance, and moderating effect of active institutional ownership. Using purposive sampling and the period of 2012-2016, we obtained 436 observations of 99 manufacturing firms for dependent variable mea- sured by ROA, and 415 observations of 95 manufacturing firms for dependent variable measured by Tobin’s Q. We found that institutional ownership had significant positive effect on firm perfor- mance. Active institutional ownership as a moderating variable, strengthens the positive effect of institutional ownership on firm performance.